2016
DOI: 10.20546/ijcrbp.2016.305.023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sugarcane (Saccharum officinarum L.) Cultivars of Republic of Benin

Abstract: A b s t r a c t A r t i c l e I n f oIn Benin, sugarcane (Saccharum officinarum L.), is both a food security and cash crop neglected by scientific research and development programs. To assess its diversity at national level, 89 farmer-named cultivars were collected from different production zones, planted in completely randomized bloc design with three repetitions and characterized using 15 qualitative and 10 quantitative morphological parameters. Data collected were analyzed using descriptive statistics and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Sugarcane stalks can reach a height of 3 to 5 meters or more. Sugarcane plant also has green, dark red, purple bark or a combination of these colours (Ekpelikpeze et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Sugarcane stalks can reach a height of 3 to 5 meters or more. Sugarcane plant also has green, dark red, purple bark or a combination of these colours (Ekpelikpeze et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Green (1), light green (2), dark green (3), yellow (4), light yellow (5), dark yellow (6), light purple (8), dark purple (9), brown (10), light brown (11), dark brown (12), yellowish green (13), greenish yellow (14), brownish green (15), brownish yellow (16), and brownish purple (17) Absent (1)…”
Section: Declarationsmentioning
confidence: 99%
“…Sugarcane breeders contemplating the use of new germplasm in breeding programs need to know the characteristics of the many classes and clones of materials available and how a logical selection of parents could be made from them (Mbuma et al, 2019). Several authors have reported that the characterization of sugarcane germplasm in different parts of the world is done merely by giving a detailed description of the morphological characters that each variety possesses (Akhtar et al, 2006;Nosheen and Ashraf, 2001;Ekpélikpézé et al, 2016). Specifically, two useful traits are indicative of high sugar yield; viz.…”
Section: Introductionmentioning
confidence: 99%